Hot-melt pressure-sensitive adhesive for seamless bonding of nylon fabric part I: effect of a functional monomer. Issue 6 (March 2019) - Kuo, Chung-Feng Jeffrey; Chen, Jiong-Bo; Lin, Pin-Hua; Yen, Hui-Ting
This study synthesized a series of prepolymers from butyl acrylate and functional monomer with various side-chain structures. A bulk polymerization process was then applied under ultraviolet irradiation. The molecular structure of the prepolymer was characterized by Fourier transform infrared spectroscopy and gel permeation chromatography. The degradation temperature and glass transition temperature ( Tg ) were examined. The prepolymer was employed to the acrylic hot-melt pressure-sensitive adhesives (HMPSAs) and the corresponding adhesive performance was presented. In this study, glycidyl methacrylate was considered to be an effective cross-linking agent for acrylic HMPSAs containing carboxylic acid groups. The prepolymer containing carboxylic acid synthesized acrylic HMPSAs exhibited high adhesion in peel strength and shear strength compared to the hydroxyethyl group. The adhesive performance of HMPSAs in different environments was also investigated.